The Dynamics of Drinking and Driving in the U.S.: The Role of Social Forces and the Role of Law - Darren Grant
Among U.S. drivers involved in fatal accidents, blood alcohol concentration conditional on drinking is static. Thus the dynamics of drunk driving can be described using the fraction of accident-involved drivers who have been drinking (HBD). Changes in this variable imply significant reductions in vehicle fatalities between 1975 and 2004, and correlate mildly with the underlying “general risk factor” that accounts for the remaining reduction in fatalities. But seven important drunk driving laws influence HBD only weakly, and together explain only one-sixth of its reduction over this period. The estimated effect of social forces over twice as large.